Factor completely 3×2 + 2x − 1. (3x + 1)(x − 1) (3x + 1)(x + 1) (3x − 1)(x + 1) (3x − 1)(x − 1)

Question

Factor completely 3×2 + 2x − 1.

(3x + 1)(x − 1)
(3x + 1)(x + 1)
(3x − 1)(x + 1)
(3x − 1)(x − 1)

in progress 0
Lyla 1 week 2021-09-14T19:52:23+00:00 2 Answers 0

Answers ( )

    0
    2021-09-14T19:53:25+00:00

    Answer:

    (3x-1)(x+1)

    Step-by-step explanation:

    3x^2 + 2x − 1= (2x=3x-x)

    3x^2 +3x-x-1=

    3x(x+1)-1(x+1)=

    (x+1)(3x-1)

    0
    2021-09-14T19:54:01+00:00

    Answer:

    C) (3x-1) (x+1)

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )